2017
DOI: 10.5459/bnzsee.50.4.595-607
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of a four storey post-tensioned concrete building subjected to shake table testing

Abstract: Prior research into low-damage wall systems has predominately focused on the walls behaviour in isolation from other building components. Although the response of these isolated walls has been shown to perform well when subjected to both cyclic and dynamic loading, uncertainty exists when considering the effect of interactions between walls and other structural and non-structural components on the seismic response and performance of entire buildings. To help address this uncertainty a computational model was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…36 Damping ratios of 2% were used for the design-level earthquake (DBE) and maximum considered earthquake (MCE) intensities, which was similar to that used in comparable UPT building models. 22 A frequency analysis of the white noise excitation at the start of testing showed that the fundamental period of the test building with the D1a configuration was 0.35 s for the first translational mode in the transverse direction, and 0.21 s for the first translational mode in the longitudinal direction. The eigen analyses of the models revealed that the fundamental periods of the transverse and longitudinal direction frames with the D1a configuration were 0.24 and 0.16 s, respectively.…”
Section: Energy Dissipation Device Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Damping ratios of 2% were used for the design-level earthquake (DBE) and maximum considered earthquake (MCE) intensities, which was similar to that used in comparable UPT building models. 22 A frequency analysis of the white noise excitation at the start of testing showed that the fundamental period of the test building with the D1a configuration was 0.35 s for the first translational mode in the transverse direction, and 0.21 s for the first translational mode in the longitudinal direction. The eigen analyses of the models revealed that the fundamental periods of the transverse and longitudinal direction frames with the D1a configuration were 0.24 and 0.16 s, respectively.…”
Section: Energy Dissipation Device Validationmentioning
confidence: 99%
“…This modeling method has been verified in prior UPT wall simulation analysis. 18,22 The multispring model was proven to capture the mechanical behavior of slotted-beam joints in component-level experiments. 29 In the multi-spring model, the top concrete hinge region was modeled by macro multiple concrete springs and longitudinal and diagonal hanger reinforcement springs.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage occurred at the wall‐to‐floor interface where the PT walls were monolithically connected to the topping of the precast floor units and crushing at the column bases occurred due to increased axial demands from outrigger framing action. A numerical model developed for the E‐defense test building showed that the inclusion of the beams connected between the wall and columns as well as in‐plane and out‐of‐plane response of the floors were essential to accurately capture the lateral‐load response of the entire building 27 . A separate unidirectional test of a three‐storey precast concrete building that incorporated hybrid PT walls was completed on the shake‐table at UC San Diego 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…A numerical model developed for the E-defense test building showed that the inclusion of the beams connected between the wall and columns as well as in-plane and out-of-plane response of the floors were essential to accurately capture the lateral-load response of the entire building. 27 A separate unidirectional test of a three-storey precast concrete building that incorporated hybrid PT walls was completed on the shake-table at UC San Diego. 28,29 Although the test primarily focused on the diaphragm response, the test confirmed that slotted connectors could be implemented between the wall and floor to enable horizontal force transfer while allowing unrestrained uplift of the PT walls.…”
Section: Introductionmentioning
confidence: 99%